Inpatient rehabilitation services for patients after stroke in Thailand: A multi-centre study - Vilai Kuptniratsaikul (2018)
Objective: To set a baseline for measuring the development of medical rehabilitation services and outcomes for patients after stroke and promoting rehabilitation medicine in Thailand. Design: Multi-centre, prospective study. Subjects: Patients after stroke in Thai Stroke Rehabilitation Registry (TSRR), aged ≥18 years, with stable medical signs, able to follow a 1-step command and sit for at least 30 min. Methods: Rehabilitation services were recorded daily as units of treatment (1 unit=20 min). Length of stay and treatment costs were calculated. Results: Of 327 patients enrolled in the study, 285 (87.2%) completed their treatment programme. Mean length of stay was 29.4 (standard deviation 17.9) days. The average number of total treatment units for stroke rehabilitation was 319.5 (range 27-1674 units), with 205 units of nursing, 40 units of physical therapy and 34 units of occupational therapy as the top 3 services provided. The mean total cost for all treatments during rehabilitation was 28,399 (standard deviation 22,511) baht (approximately USD 789). The ratio of costs not related to rehabilitation to those related to rehabilitation was approximately 2:1. Conclusion: This study reports the baseline for measuring the development of rehabilitation services for patients after stroke with a mean length of stay of one month, and for estimating the reasonable costs. © 2009 The Authors.